Target-induced activation of DNAzyme for highly sensitive colorimetric detection of bleomycin via DNA scission. Issue 29 (22nd June 2022) - Liao, Xiaofei; Li, Mengyan; Zou, Li
Abstract : A label-free and sensitive colorimetric strategy for bleomycin detection was developed based on target-induced activation of DNAzyme via DNA scission. Abstract : In this work, a label-free and sensitive colorimetric sensing strategy for the detection of bleomycin (BLM) was developed on the basis of BLM-mediated activation of G-quadruplex DNAzyme via DNA strand scission. A G-quadruplex based hairpin probe (G4HP) containing the scission site (5′-GT-3′) of BLM at the loop region and guanine (G)-rich sequences at its 5′-end was employed in this protocol. In the presence of BLM, it may cleave the 5′-GT-3′ site of the hairpin probe with Fe(ii ) as a cofactor, releasing the G-tetrads DNA fragment, which may further bind hemin to form a catalytic G-quadruplex-hemin DNAzyme. The resultant G-quadruplex DNAzyme has notable peroxidase-like activity, which effectively catalyzes the oxidation of 2, 2′-azino-bis(3-ethylbenzothiozoline-6-sulfonic acid) (ABTS) by H2 O2 to produce the blue-green-colored free-radical cation (ABTS ·+ ). Therefore, the detection of BLM can be achieved by observing the color transition with the naked eye or measuring the absorbance at a wavelength of 420 nm using a UV-Vis spectrophotometer. Attributing to the specific BLM-induced DNA strand scission and the effective locking of G-tetrads in the stem of the G4HP, the colorimetric sensing strategy exhibits high sensitivity and selectivity for detection of BLM in human serum samples, which might hold great promise for BLM assay in biomedical and clinical research.